2015
DOI: 10.1007/s12602-015-9189-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Probiotic Bacillus spp. in Rotifer (Brachionus plicatilis) and Artemia (Artemia urmiana) Enrichment: Effects on Growth and Survival of Pacific White Shrimp, Litopenaeus vannamei, Larvae

Abstract: This study was to evaluate the effect of a preparation of Bacillus probiotic (Bacillus licheniformis and B. subtilis, 1:1) on growth and survival rate of Pacific white shrimp, Litopenaeus vannamei larvae. The larvae were fed on Artemia urmiana nauplii and Brachionus plicatilis enriched with the probiotic preparation at 1 × 10(6) CFU mL(-1) rate. The experimental setup was completely randomized design comprised of six treatments, namely solo Artemia nauplii (A) or rotifer (R), Artemia nauplii and rotifer withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…In the current study, a diet that included both enriched rotifers and Artemia with probiotics increased survival and metamorphosis rates of megalopa compared to a diet without enriched live food. The same results were obtained in L. vannamei fed both enriched rotifer and Artemia (Jamali et al, 2015). Total bacteria and probiotic Bacillus increased in the host (Jamali et al,, 2015) that resulted in increasing activity of digestive enzymes (Ziaei-Nejad et al, 2005) and inhibiting the growth of pathogens (Decamp et al, 2008), which in turn improved larval survival.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In the current study, a diet that included both enriched rotifers and Artemia with probiotics increased survival and metamorphosis rates of megalopa compared to a diet without enriched live food. The same results were obtained in L. vannamei fed both enriched rotifer and Artemia (Jamali et al, 2015). Total bacteria and probiotic Bacillus increased in the host (Jamali et al,, 2015) that resulted in increasing activity of digestive enzymes (Ziaei-Nejad et al, 2005) and inhibiting the growth of pathogens (Decamp et al, 2008), which in turn improved larval survival.…”
Section: Discussionmentioning
confidence: 52%
“…The same results were obtained in L. vannamei fed both enriched rotifer and Artemia (Jamali et al, 2015). Total bacteria and probiotic Bacillus increased in the host (Jamali et al,, 2015) that resulted in increasing activity of digestive enzymes (Ziaei-Nejad et al, 2005) and inhibiting the growth of pathogens (Decamp et al, 2008), which in turn improved larval survival. In addition, Nogami et al (1997) reported that the bacterial strain PM-4 (Thalassobacterutilis), which was added daily into rearing water increased the survival of swimming crab (Portunus trituberculatus) larvae by repressing the growth of harmful bacteria and fungi.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…not only has a proper size and great nutritional value but also is an adequate vehicle to deliver other substances such as nutrients, antimicrobials, vaccines and probiotics (AZIMIRAD et al, 2016;JAMALI et al, 2015). Thus, in the first stage of this investigation, it was proved that all strains remain viable in the water of the experimental units with no significant modifications in the number of viable cells after 4 hours.…”
Section: Resultsmentioning
confidence: 75%
“…This effect on body weight was often, but not always, accompanied by a decreased feed conversion ratio (FCR) (Zokaeifar et al, 2012) or higher survival rate (Shen et al, 2010), or the results were inconsistent (Franco et al, 2017). There are examples in the literature where probiotic applications did not affect growth parameters, but authors reported beneficial effects on the survival of Litopenaeus vannamei larvae (Jamali et al, 2015).…”
mentioning
confidence: 99%